Energy-efficient Artificial Intelligence through Neuromorphic Architectures - Teja Sri, Mutchakarla; Harshitha, N.; Mohana, A.; Chandra Sekhar Koppireddy (Journal of Innovations in Data Science and Big Data Management, 2025)
The push for energy-efficient adaptable processing keeps growing as AI gets integrated into everything from cloud systems to smart devices and autonomous technologies. Neuromorphic computing mimics how brains operate, using spiking neural networks in custom hardware that acts like communicating neurons. This approach allows machines to process data in parallel while responding quickly and using minimal power instead of draining it heavily. The biggest perks include significantly lower energy consumption—potentially 10 to 1,000 times less than standard chips, maybe even 100k times less if matching human brain efficiency levels. This enables gadgets to handle AI locally without relying on cloud backups, ideal for IoT devices, wearables, robots, and self-driving vehicles that require real-time responses. Continuous learning is another advantage. Systems adapt dynamically using live data streams instead of requiring pauses for retraining cycles. Timing precision matters too—these setups excel at spotting patterns in voice signals, sensor data, or detecting unusual financial activities. Creating artificial brains that behave like biological ones remains challenging, though. Programming tools are still underdeveloped, scaling to billions of neurons is not fully achievable yet, and training methods need specialised adjustments compared to conventional AI approaches.